Development of Standard Operating Procedures for Non-Population Administrative Services at Pisugi District Office, Jayawijaya Regency - Sukmawati, Sukmawati; Rijal, Rijal; Suleman, Sukur (Program Pascasarjana Universitas Negeri Makassar, 2025)
This study analyzes the implementation of Standard Operating Procedures (SOP) in non-population administrative services in Pisugi District, Jayawijaya Regency, Papua Pegunungan, using a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving nine key informants, consisting of the district head, service officials, and service users. The analysis applied the SERVQUAL framework (tangibles, reliability, responsiveness, assurance, and empathy) to examine gaps between service expectations and realities. The findings indicate that SOP implementation in Pisugi District faces major challenges. Service facilities are available but limited, and SOPs are not publicly accessible, undermining transparency. Service reliability is low due to inconsistent completion times, while responsiveness is constrained by limited staffing and non-standardized communication, despite officials’ efforts to explain procedures. The assurance dimension is weakened since SOPs serve only as internal guidelines, leading citizens to question service legitimacy. Empathy is demonstrated through friendliness and use of local languages, but remains inconsistent due to human resource constraints. The novelty of this research lies in its focus on non-population administrative services in remote Papua, a context rarely explored in prior studies. It extends SERVQUAL theory by showing that in remote areas, service quality is not only shaped by physical facilities and officials’ behavior but also by SOP transparency, institutional capacity, and socio-geographic conditions. The study highlights the need for greater procedural transparency, publication of SOPs, and bureaucratic adaptation to local contexts.